Artemisinic acid exhibits antitumor activity in MCF-7 breast cancer cells through the inhibition of angiogenesis, VEGF, m-TOR and AKT signalling pathways (Bangladesh Journal of Pharmacology, 2016)
The aim of the present study was to evaluate the antitumor and anti-angiogenic effects of artemisinic acid in MCF-7 human breast cancer cells. Various cell signalling pathways (VEGF, m-TOR and AKT signalling pathways) and MTT assay were used. The in vivo antitumor activity of artemisinic acid was evaluated by means of tumor xenograft mouse model. Transwell cell migration assay was used to examine the chemotactic motility of the human umbilical vascular endothelial cells (HUVECs), while as endothelial cell capillary-like tube formation assay was used to evaluate the effect of artemisinic acid on the tube formation in HUVECs. We found that artemisinic acid considerably reduced both the volume and weight of concrete tumors and reduced angiogenesis in a xenograft mouse tumor model in vivo. Further, artemisinic acid suppressed the VEGF-induced cell migration and capillary-like tube formation of HUVECs in a dose-dependent manner. Artemisinic acid was found to suppress the VEGF-induced phosphorylation of VEGFR2 and also the activity of AKT and m-TOR.Video Clip of Methodology:Western blot assay: 4 min 33 sec   Click to watch